2022
DOI: 10.1093/jbcr/irac169
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Garlic and Turmeric for the Diabetic Wound Healing in Mice

Abstract: Diabetes is involved in delayed wound healing that can be cured by natural products such as garlic, turmeric, and fibroin extracts. Alloxan monohydrate is used for inducing diabetes in mice. The percent wound contraction of garlic (150 mg/ml), turmeric (100 mg/ml), and fibroin (50 mg/ml), individually and in combinations garlic (150 mg/ml) + fibroin (50 mg/ml), turmeric (100 mg/ml) + fibroin (50 mg/ml), garlic (150 mg/ml) + turmeric (100 mg/ml), and garlic (150 mg/ml) + turmeric (100 mg/ml) + fibroin (50 mg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…[58] Farooq et al evaluated the effects of garlic extract, turmeric extract, and silk fibroin solution on the wound healing of diabetic mice. [229] They applied these agents separately or in combination to the wounds and compared them with a control group that received PBS. They measured the serum levels of MMP-2, -7, and -9 after the wounds healed and found that they were lower in the treatment groups than in the control group.…”
Section: Influence Of Topical Treatments In Humans and Animals On Pro...mentioning
confidence: 99%
“…[58] Farooq et al evaluated the effects of garlic extract, turmeric extract, and silk fibroin solution on the wound healing of diabetic mice. [229] They applied these agents separately or in combination to the wounds and compared them with a control group that received PBS. They measured the serum levels of MMP-2, -7, and -9 after the wounds healed and found that they were lower in the treatment groups than in the control group.…”
Section: Influence Of Topical Treatments In Humans and Animals On Pro...mentioning
confidence: 99%